ANALISIS PENGARUH DIGITALISASI PELAYANAN PUBLIK BANK XYZ TERHADAP PENGALAMAN DAN KEPERCAYAAN NASABAH - Fazira, Nadia Nur; Wolor, Christian Wiradendi; Utari, Eka Dewi (Fakultas Ekonomi dan Bisnis, 2025)
Digitalization has now become a key factor in improving the efficiency and quality of public services in various sectors, including banking. This study aims to analyze the effect of digitalization on public services at Bank Xyz. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to customers and interviews with the bank. The main variables analyzed include ease of service access, transaction efficiency, customer satisfaction, and challenges in implementing digitalization. The results of the study show that digitalization contributes significantly to increasing the speed and convenience of banking services, but still faces obstacles such as mobile application constraints, data security and customer trust. Thus, this study provides insight for banks in optimizing digital transformation to improve the quality of public services. Keywords: Digitalization, Public Services, Banking Services, Mobile Banking, Customer Trust, Customer Satisfaction